2014
DOI: 10.1159/000365751
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Molecular Benchmark of Physiological Intestinal Anastomotic Healing in Rats: An Experimental Study

Abstract: Purpose: This investigation focuses on the physiological characteristics of gene transcription of intestinal tissue following anastomosis formation. Methods: In eight rats, end-to-end ileo-ileal anastomoses were performed (n = 2/group). The healthy intestinal tissue resected for this operation was used as a control. On days 0, 2, 4 and 8, 10-mm perianastomotic segments were resected. Control and perianastomotic segments were examined with an Affymetrix microarray chip to assess changes in gene regulation. Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, various studies have convincingly suggested a positive effect of IGF-1 on the process of anastomotic healing. Furthermore, in a previous study, we observed a significant increase in local IGF-1 gene expression during intestinal anastomotic healing [ 22 ]. Therefore, it may not be excluded that pasireotide negatively impacts physiological anastomotic healing via decreasing systemic and/or local IGF-1 production.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, various studies have convincingly suggested a positive effect of IGF-1 on the process of anastomotic healing. Furthermore, in a previous study, we observed a significant increase in local IGF-1 gene expression during intestinal anastomotic healing [ 22 ]. Therefore, it may not be excluded that pasireotide negatively impacts physiological anastomotic healing via decreasing systemic and/or local IGF-1 production.…”
Section: Introductionmentioning
confidence: 91%
“…This may be explained by local release mechanisms that bypass pasireotide dependent central nervous inhibition of the GH-IGF-1 axis. We have shown that a complex machinery of IGF-1, its receptors, and a large group of IGF-1 binding proteins is upregulated in the intestine during anastomotic healing [ 22 ]. It remains unclear how dependent this upregulation is of upstream hormonal stimulation and to which degree this is an autonomous, immune system–mediated effect.…”
Section: Bursting Pressure and Igf-1 Levelsmentioning
confidence: 99%